PERKEMBANGAN USAHA MIKRO SEBELUM DAN SESUDAH MEMPEROLEH PEMBIAYAAN MURABAHAH DARI BMT KOTA MANDIRI BENGKULU - Afrianty, Nonie (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2018)
businesses can develop with additional capital, so it is necessary to know whether there are differences in the development of micro-enterprises before and after obtaining murabahah financing from BMT Kota Mandiri Bengkulu. The types of data in this study are primary data and secondary data. Data collection techniques used were oral interviews and library research. In this study, 33 samples were taken with the Puposive sampling technique with the characteristics of financing customers who had run murabahah financing for at least six months. Data Analysis Techniques in the normality test using the Kolmogorov-Smirnov method and homogeneity test with the Levene method. on testing hypotheses using paired sample t-test parametric statistics. The conclusion of this study is that there are differences in the development of micro-enterprises before and after obtaining murabahah financing from BMT Kota Mandiri Bengkulu.